Evaluación analítica para la determinación de sulfatos en aguas por método turbidimétrico modificado - Severiche, Carlos A (Editorial Bonaventuriana, 2018)
The goal of a chemical analysis of water is to produce accurate and reliable results, being the validation of tests one of the most important aspects to achieve this purpose, it also constitutes a key factor in the provision of analytical services. Determination of sulfate ion in water is one of the most discussed analytical methodologies in the scientific-technical sphere of waters analysis, mainly because of the disadvantages of internationally accepted methods (gravimetric, turbidimetric and chromatographic). In this study was made the evaluation of turbidimetric analytical method for the determination of sulfate in water, the aim was to include a modification to the standardized method and confirm the correct application of modified method for water analysis. We have worked on samples of different water types: drinking water, waste water, shallow, pit and pool, strictly complying the validation protocols. Satisfactory results were found regarding to precision and accuracy in order to give real and reliable results for the analyzed sample.